Overexpression of a high-affinity nitrate transporter OsNRT2.1 increases yield and manganese accumulation in rice under alternating wet and dry condition - Luo, Bingbing; Chen, Jingguang; Zhu, Longlong; Liu, Shuhua; Li, Bin; Lu, Hong; Ye, Guoyou; Xu, Guohua; Fan, Xiaorong (Frontiers Media, 2018)
Nitrate and manganese (Mn) are necessary elements for the growth and development of rice in paddy soil. Under physiological conditions, we previously reported that the uptake of Mn in roots can be improved by the addition of external nitrate but not ammonium. To investigate the mechanism(s) of this phenotype, we produced plant lines overexpressing OsNRT2.1 and assessed Mn uptake under alternating wet and dry (AWD) and waterlogged (WL) conditions. Under AWD condition, we observed a 31% reduction in grain yields of wild type (WT) plants compared to WL condition. Interestingly, the overexpression of OsNRT2.1 could recover this loss, as OsNRT2.1 transgenic lines displayed higher grain yields than WT plants. We also observed 60% higher grain Mn in the transgenic lines in AWD condition and approximately 30% higher Mn in the grain of transgenic lines in WL condition. We further found that the overexpression of OsNRT2.1 did not alter Mg and Fe in the seeds in either growth condition. The reasons for the increased Mn content in OsNRT2.1 transgenic seeds in AWD condition could be explained by the elevated expression of OsNRAMP family genes including OsNRAMP3, OsNRAMP5, and OsNRAMP6 in node I, the panicle-neck, and the flag leaves. The mechanism(s) underpinning the upregulation of these genes requires further investigation. Taken together, our results provide a new function of OsNRT2.1 in improving rice yields and grain Mn accumulation during water-saving cultivation patterns. This represents a new strategy for maintaining yield and improving food quality in a sustainable agricultural system.